Political cycle and the financial lending scale. Issue 6 (30th March 2022) - Wang, Meng-Ying; Chou, Li-Chen
ABSTRACT: We study the impact of the political cycle on financial lending. The change of party secretaries every several years in the Chinese cities provides a good setting for our analysis. Empirical results indicate the scale of lending by financial institutions increased one year before and after the congress of the Chinese Communist Party and decreased during the convening year, showing political cyclicality. In addition, the size of financial lending by the cities whose party secretary's age is over 55 is smaller than others. The results reflect the incentive to achieve promotion by stimulating economic performance is smaller for the ageing secretary.